Ergo-Technopreneurship Training to Improve Knowledge and Attitude of Technology Entrepreneurs Palembang Local Culinary Traders - Setiawan, Heri; Susanto, Sani; Rinamurti, Micheline; Alfian, Achmad; Pratama, Yohanes Dicka; Budiarto, Dominikus; Clara, Catharina (Jurnal Ekuisci, 2025)
Aim. The research objective is to empower the community through Palembang local culinary businesses for the process of developing and implementing innovative ideas that use technology to create new products, services, or businesses that have the potential to grow and develop attitudes of mastery of technology and entrepreneurship and income of Palembang local culinary traders. Methods. The methodology combined the Systemic, Holistic, Interdisciplinary, and Participatory (SHIP) approach and quasi-experimentation. The study employed a post-test-only group design (treatment by subject design). Identifying the issue was the first step in the activities, followed by problem prioritization and action plan creation. As a research intervention, this action plan was implemented. After determining the percentage of change, the acquired data were descriptively analyzed using a paired t-test. Result. The findings indicated that merchants' income grew by 29.69% (p<0.05), and technology entrepreneurs' attitude scores increased by 37.45%. This demonstrates that community empowerment through a participative method is highly effective. Conclusion. Starting from the results of the analysis and discussion reviewed based on relevant literature, it can be concluded: (1) the strategy of community empowerment through ergo-technopreneurship training is quite adequate, as seen from the enthusiasm of culinary traders to develop their business; (2) Ergo-technopreneurship training can significantly expand the understanding of community empowerment of local Palembang culinary traders in the field of ergonomics-based technology entrepreneurial strategies by 37.45% (p < 0.05); and (3) Training in ergo-technopreneurship for community empowerment can significantly increase the technology entrepreneurial attitudes of local Palembang culinary traders by 29.69% (p < 0.05).